1985
DOI: 10.1007/bf00261587
|View full text |Cite
|
Sign up to set email alerts
|

Intra-renal reflux

Abstract: A new model for the study of intra-renal reflux (IRR) is proposed. The renal pelvis of human kidneys, either obtained from cadavers or removed surgically, was injected, at increasing pressures, with dye solutions to investigate intra-renal reflux. To reproduce physiological conditions as closely as possible, arterial perfusion was performed, either continuously or by means of a peristaltic pump, so that a predetermined pressure in the vascular system could be obtained. Comparison was made between results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Boccafoschi et al [5] demonstrated that intrarenal reflux occurred on human cadaver kidneys at pressures under 30 mmHg. They also showed that when the intrarenal pressure was raised to 37-52 mmHg, pyelovenous reflux occurred; this refux is typically related to infection.…”
Section: Discussionmentioning
confidence: 98%
“…Boccafoschi et al [5] demonstrated that intrarenal reflux occurred on human cadaver kidneys at pressures under 30 mmHg. They also showed that when the intrarenal pressure was raised to 37-52 mmHg, pyelovenous reflux occurred; this refux is typically related to infection.…”
Section: Discussionmentioning
confidence: 98%
“…The potential consequences of high pressures in the upper urinary tract have previously been studied [2,3,6]. A high constant intrarenal pressure increases the severity of intrarenal backflow and may result in infectious complications and damage to the kidney parenchyma [1,5,6,8]. Immediate postoperative complications, including sepsis, have been identified in 13.3% of patients undergoing ureteroscopy [16Á18].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged upper urinary tract obstruction and surgical irrigation will lead to increased pressure of the renal pelvis. When the intrapelvic pressure exceeds 40 cm H 2 O, the contents of the renal pelvis system go beyond its limit, initiating pyelosinus, pyelovenous, pyelolymphatic backflow, and/or irrigation fluid absorption [19][20][21]. Increased intrapelvic pressure has been proven to be a major risk factor for postoperative fever and urosepsis [22].…”
Section: Discussionmentioning
confidence: 99%